Climate Change and Sustainable Tourism: South Africa caught in-between. - Professor L. Amusan; O. Olutola (African Journal of Hospitality, Tourism and Leisure, 2017)
Climate change and tourism are symbolically two-sides of a coin. While climate change portends serious threats to ecosystems and biodiversity (the world's foremost tourism assets), environmental impacts associated with tourism-related activities significantly add to climate change. Caught in between the two scenarios is South Africa’s position as both a contributor and one of those hard-hit by climate change on the one hand, and a leading tourist destination with the country’s tourism industry representing a key economic sector and growth enabler by way of its contribution directly to Gross Domestic Product (GDP) on the other. This is beside the fact that a relatively significant share of tourism-related activities is undertaken in emerging countries, of which South Africa is one. Thus, building on the theoretical underpinnings of Green Theory and a review of relevant documents, this article assesses South African tourism and its contribution to incentivise economic growth and sustainable development, given the country's situational complexity. It argues that tourism is at the centre of a climate-energy interlock in South Africa.